Effectiveness of Tourism Sector Retribution as an Effort to Increase Local Revenue Bantaeng City (Case Study on Bantaeng Regency Tourism Office) - Agusdiwana Suarni; Mahmud Nuhung; Syahrani Mutmainnah (Jurnal Riset Perpajakan: Amnesty, 2024)
This study aims to determine the effectiveness of the regional tourism sector levy as an effort to increase the local revenue of Bantaeng city (Case study at the Bantaeng Regency Tourism Office). the type of research used is Qualitative Research Method. The data processed by the author is the result of interviews with the Bantaeng Regency Tourism Office. The data collection techniques used in this research are Documentation Techniques and Interview Techniques where the author meets face to face with the source. The result of this research shows that the average level of effectiveness of tourism sector levy revenue in Bantaeng Regency for the last 6 years is 38% which is classified as quite good criteria. However, it did not experience a significant increase in each year. To overcome the obstacles to the acceptance of retribution in the tourism sector of Bantaeng Regency, efforts are made, among others: Exploring the potential of other tourist objects and creating other vehicle attractions to attract visitors, Structuring and developing the potential of tourist objects by arranging facilities and infrastructure in potential tourist areas, and Increasing marketing and tourism promotion, both through print media and the internet. These efforts are made to attract many visitors to various tourist attractions so that they can increase the original regional income (PAD) of Bantaeng Regency.